Regulation of circadian rhythm and sleep by miR‐375‐timeless interaction in Drosophila. Issue 12 (20th October 2020) - Xia, Xiju; Fu, Xiaonan; Du, Juan; Wu, Binbin; Zhao, Xianguo; Zhu, Jinsong; Zhao, Zhangwu
Abstract: MicroRNAs are important coordinators of circadian regulation that mediate the fine‐tuning of gene expression. Although many studies have shown the effects of individual miRNAs on the circadian clock, the global functional miRNA‐mRNA interaction network involved in the circadian system remains poorly understood. Here, we used CLEAR (Covalent Ligation of Endogenous Argonaute‐bound RNAs)‐CLIP (Cross‐Linking and Immuno‐Precipitation) to explore the regulatory functions of miRNAs in the circadian system by comparing the miRNA‐mRNA interactions between Drosophila wild‐type strain W 1118 and a mutant of the key circadian transcriptional regulator Clock ( Clk jrk ). This experimental approach unambiguously identified tens of thousands of miRNA‐mRNA interactions in both the head and body. The miRNA‐mRNA interactome showed dramatic changes in the Clk jrk flies. Particularly, among ~300 miRNA‐mRNA circadian relevant interactions, multiple interactions involving core clock genes pdp1, tim, and vri displayed distinct changes as a result of the Clk mutation. Based on the CLEAR‐CLIP analysis, we found a novel regulation of the circadian rhythm and sleep by the miR‐375‐timeless interaction. The results indicated that Clk disruption abolished normal rhythmic expression of miR‐375 and the functional regulation occurred in the l‐LNv neurons, where miR‐375 modulated the circadian rhythm and sleep via targeting timeless . This work provides the first global view of miRNA regulation in the circadian rhythm.